IMPROVING FARMERS WELFARE BY ENHANCING THE ABILITY OF INFORMATION TECHNOLOGY ADOPTION: AN EVENT STUDY OF FOOD CRISIS’ THREAT - Ernawatiningsih, Ni Putu Lisa; Sri Budhi, Made Kembar; Marhaeni, Anak Agung Ngurah; Yuliarmi, Ni Nyoman (AIBPM Publisher, 2023)
Food security has become a global problem in the midst of a war which resulted in an increase in fuel prices followed by an increase in the price of basic necessities, especially our main staple food, namely rice. Overcoming this, the government is expected to pay attention to the welfare of farmers so that farmers are still able to produce to be able to meet food needs in the country. This requires the government's attention in providing counseling and training to farmers in increasing their ability to adopt technology to be applied in the agricultural sector so that production output can be increased and maintain sustainability in the domestic agricultural sector. Technology adoption theory is the main focus in improving the welfare of farmers, this is due to the benefits of information technology as a supporting sector in the production process so as to be able to increase output in a shorter span of time. The higher the ability of farmers to adopt technological developments, the higher their ability to cultivate production land which is able to increase production yields so that it will be followed by an increase in farmer welfare.